Math poster with augment reality to increase learning outcome of students' high school - Qomario Qomario; Ahmad Tohir; Cendy Prastyo (IIES Independent, 2022)
Augmented Reality-based mathematics poster is one of the media for learning mathematics with the use of technology. The rapid development of technology requires education to innovate learn-ing devices with technology, this learning media is made as a form of developing technolo-gy-based learning tools that are in accordance with educational needs. This study aims to deter-mine the feasibility and effectiveness of mathematical posters on building materials using Aug-mented Reality (AR). The subjects of this study were students of Class X SMA. This type of re-search ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The results of this study show that the Mathematics Poster for Building Spaces with Augmented Reality is "Very Appropriate" with a value given by Design and Technology experts in the "Good" category with a feasibility presentation of 89% in the "Eligible" category. The results of the validation of mathema-ticians in the "Very Good" category and a feasibility presentation rate of 93% in the "Very Eligible" category. The results of the teacher assessment are in the "Very Good" category and the feasibility presentation rate is 94% with the "Very Eligible" category. And based on the results of the pretest and posttest, it was found that there was an increase in student learning outcomes in the material of building space.